Konflik Sosial dalam Novel Orang-Orang Pulau Karya Giyan: Kajian Sosiologi Sastra dan Implementasinya sebagai Bahan Ajar Sastra di SMA N Gondangrejo - Muttaqin, Afif Khoirul; , Drs. Adyana Sunanda, M.Pd (2017)
The purpose of this study was to describe, (1) the structure of the building novel Orang-orang PulauGiyan work, (2) social conflict in the novel, and (3) implementation of research results in teaching Literature at SMAN Gondangrejo. The method used is descriptive kualitatif.Objek studies in this novel is the social conflict. Data needed in this study a paragraph in the novelOrang-orang Pulau. Sources of primary data obtained from noveOrang-orang Pulau l. Data collection techniques used using techniques catat.Teknik consider the validity of the data used is the technique of triangulation data. Data were analyzed using the methods of dialectics. Based on the analysis performed, there are three results of the study, namely (1) the structure of the building novelOrang-orang Pulau include figures that Darso and Supini, the plot forward, setting a place in the villages of Katapang for 22 years, and themes include social inequality, ( 2) social conflicts contained in the novel include arguing the dispute and humbled characterize people always deify matter, the environment is restricted by the rich and the poor, education is very backward, and (3) the implementation of the results of this research with the study of literature in class XI 1st half accordance SK 7 KD 7.2 to Education Unit Level Curriculum (SBC) and in the first semester of grade XII related to the text of fiction for Curriculum 2013.